Study of the electron lithography parameters by AFM - Myrzabekova, M.М.; Guseinov, N.R.; Zaitsev, S.I.; Shabelnikova, Ya.L.; Muratov, M.M.; Muradova, S.R.; Turarbaeva, T.B. (Recent Contributions to Physics, 2019)
The paper considers one of the methods of micro - and nano - images formation with high accuracy of process control – electronic lithography. Comparing to other nanostructuring technologies, such as photolithography in particular, electronic lithography is more versatile. This paper describes the technological processes of electron lithography on a silicon substrate using a polymer-based resist PMMA. The irradiation was carried out in the SEM chamber by electrons with an energy of 5 keV, 15 keV, 30 keV and an exposure dose of 1-10000 µС/cm2. The analysis of the obtained samples using optical and atomic force microscopy (AFM) showed the dependence of the color and the corresponding thickness of the resist on the radiation dose. The calculation of such parameters as positive and negative sensitivity and contrast was carried out on the basis of the resist thickness profiles.